2022
DOI: 10.3390/jpm12040635
|View full text |Cite
|
Sign up to set email alerts
|

Association between Glasgow Coma Scale in Early Carbon Monoxide Poisoning and Development of Delayed Neurological Sequelae: A Meta-Analysis

Abstract: A significant number of people experience delayed neurologic sequelae after acute carbon monoxide (CO) poisoning. The Glasgow Coma Scale (GCS) can be used to predict delayed neurologic sequelae occurrence efficiently and without any restrictions. Here, we investigated the association between a low GCS score observed in cases of early CO poisoning and delayed neurologic sequelae development through a meta-analysis. We systematically searched MEDLINE, EMBASE, and the Cochrane Library for studies on GCS as a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Previous studies have suggested an association between a GCS score < 9 and the development of DNS and/or ABLs 22 , 23 , 32 . Results from our study were comparable.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have suggested an association between a GCS score < 9 and the development of DNS and/or ABLs 22 , 23 , 32 . Results from our study were comparable.…”
Section: Discussionmentioning
confidence: 95%
“…39,40 Moreover, a meta-analysis including 2328 patients from 10 studies demonstrated that patients with initial low GCS score had higher risk for developing DNS compared to those with higher GCS score. 41 Future studies may explore the different contributions of each variable to GPN.…”
Section: Discussionmentioning
confidence: 99%
“…Este cuadro aparece entre 3 y 40 días después de la exposición inicial, y se manifiesta de forma plural y variable en forma de apatía, deterioro de la memoria, desorientación, mutismo, irritabilidad, incapacidad para concentrarse, cambios de personalidad, labilidad emocional, neuropatía, incontinencia, corea, apraxia, psicosis, demencia y parkinsonismo [9][10][11] . En la actualidad aún no están bien definidos los criterios de confirmación diagnóstica ni los mecanismos que ocasionan el SNT, aunque algunos autores han relacionado recientemente su aparición con puntuaciones bajas en la Escala del Coma de Glasgow (ECG) en la fase aguda de la intoxicación 12 . La detección de daños en la sustancia blanca y el hipocampo o fenómenos de desmielinización en las resonancias magnéticas de pacientes con SNT apoyarían esta teoría [12][13][14][15] .…”
Section: Contribución De Los Autoresunclassified
“…En la actualidad aún no están bien definidos los criterios de confirmación diagnóstica ni los mecanismos que ocasionan el SNT, aunque algunos autores han relacionado recientemente su aparición con puntuaciones bajas en la Escala del Coma de Glasgow (ECG) en la fase aguda de la intoxicación 12 . La detección de daños en la sustancia blanca y el hipocampo o fenómenos de desmielinización en las resonancias magnéticas de pacientes con SNT apoyarían esta teoría [12][13][14][15] . Otras teorías propuestas relacionan su desarrollo con algunos factores predisponentes: edad avanzada, duración de la exposición, retraso en el inicio del tratamiento, el estrés oxidativo con incremento de las concentraciones de lactato o presencia de hipertermia, pero no existe un consenso claro 12,[16][17][18] .…”
Section: Contribución De Los Autoresunclassified